Learning foreign languages in teletandem: Resources and strategies - Telles, João A. [UNESP] (FapUNIFESP (SciELO), 2015)
Teletandem is a virtual, collaborative, and autonomous context in which two speakers of different languages use the text, voice, and webcam image resources of VOIP technology (Skype) to help each other learn their native language (or language of profi ciency). This paper focuses on learners' studying processes and their responses to teletandem. We collected quantitative and qualitative data from 134 university students through an online questionnaire. Results show the content of students' learning processes, resources, activities, and strategies. We conclude with a critical discussion of the results and raise pedagogical implications for the use o-f teletandem as a mode of online intercultural contact to learn foreign languages.
Keywords: Foreign language; Foreign language teaching and learning; Tandem learning; Telecollaboration; Teletandem